Cardioprotective effects of genetically engineered cardiac stem cells by spheroid formation on ischemic cardiomyocytes - Jeong, Han Saem (Mol Med, 2020)
BACKGROUND: Sca-1+ cardiac stem cells and their limited proliferative potential were major limiting factors for use in various studies. METHODS: Therefore, the effects of sphere genetically engineered cardiac stem cells (S-GECS) inserted with telomerase reverse transcriptase (TERT) were investigated to examine cardiomyocyte survival under hypoxic conditions. GECS was obtained from hTERT-immortalized Sca-1+ cardiac stem cell (CSC) lines, and S-GECS were generated using poly-HEMA. RESULTS: The optimal conditions for S-GECS was determined to be 1052 GECS cells/mm(2) and a 48 h culture period to produce spheroids. Compared to adherent-GECS (A-GECS) and S-GECS showed significantly higher mRNA expression of SDF-1α and CXCR4. S-GECS conditioned medium (CM) significantly reduced the proportion of early and late apoptotic cardiomyoblasts during CoCl(2)-induced hypoxic injury; however, gene silencing via CXCR4 siRNA deteriorated the protective effects of S-GECS against hypoxic injury. As downstream pathways of SDF-1α/CXCR4, the Erk and Akt signaling pathways were stimulated in the presence of S-GECS CM. S-GECS transplantation into a rat acute myocardial infarction model improved cardiac function and reduced the fibrotic area. These cardioprotective effects were confirmed to be related with the SDF-1α/CXCR4 pathway. CONCLUSIONS: Our findings suggest that paracrine factors secreted from transplanted cells may protect host cardiomyoblasts in the infarcted myocardium, contributing to beneficial left ventricle (LV) remodeling after acute myocardial infarction (AMI).